Technopedagogical Design of Electronic Learning Portfolios: An Experience with Undergraduate Students - Frida Díaz Barriga Arceo; Eric Romero Martínez; Abraham Heredia Sánchez (Universidad Autónoma de Baja California, 2012)
In this article the technopedagogical design of electronic learning portfolios with eighteen undergraduate psychology students is reported. The e-portfolio model is based on the approach of situated learning and authentic assessment, and relies on the metaphors of the portfolio as mirror, map and sonnet. It includes a description of the e-portfolio; the skills and learnings expected of the student; key questions for reflection; minimum input required; the type of evidence or artifacts expected; and the technological resources employed. Examples of the students' reflections and of the self-assessments and co-assessments performed are provided. The findings suggest that e-learning portfolios enable the recovery and systematization of learning productions and experiences, and can function as a tool for monitoring learning as well as for reflection on the individual's own professional identity, personal and academic trajectory.